2015
DOI: 10.1371/journal.pone.0143372
|View full text |Cite
|
Sign up to set email alerts
|

Parental Effect of Long Acclimatization on Thermal Tolerance of Juvenile Sea Cucumber Apostichopus japonicus

Abstract: To evaluate the thermal resistance of marine invertebrates to elevated temperatures under scenarios of future climate change, it is crucial to understand parental effect of long acclimatization on thermal tolerance of offspring. To test whether there is parental effect of long acclimatization, adult sea cucumbers (Apostichopus japonicus) from the same broodstock were transplanted southward and acclimatized at high temperature in field mesocosms. Four groups of juvenile sea cucumbers whose parents experienced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Previous research on juvenile sea cucumbers, Apostichopus japonicas, has suggested that increased exposure of parental generations to heat variations will increase the upper thermal limit of their offspring [32]. Similarly, transgenerational mechanisms could improve the tolerance of several holothuroid species during future warming events.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on juvenile sea cucumbers, Apostichopus japonicas, has suggested that increased exposure of parental generations to heat variations will increase the upper thermal limit of their offspring [32]. Similarly, transgenerational mechanisms could improve the tolerance of several holothuroid species during future warming events.…”
Section: Discussionmentioning
confidence: 99%
“…The sea cucumber A. japonicus in the northern China experienced the highest temperature between 26 and 30 °C in the field [ 11 ]. Besides, A. japonicus enters a state of aestivation when the ambient temperature is maintained at 26 °C [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, if offspring to parents that developed during, or later experienced, a heat wave are born "heat tolerant, " they might be maladapted to the normally colder temperatures of their habitat. Work on ectotherms (e.g., Wang et al, 2015) and plants (e.g., Li and Brawley, 2003) show that parents exposed to warm temperature sire offspring that are more heat-tolerant. To the best of our knowledge, there are no corresponding data for endotherms.…”
Section: Future Perspectivesmentioning
confidence: 99%